Estimation of stray coupling capacitances in biopotential measurements - Haberman, Marcelo Alejandro (2011)
Biopotential measurements are very sensitive to electromagnetic interference (EMI) from power-lines. Interference conditions are mainly imposed by electric-field coupling, whose effects can be described by coupling capacitances. The main of them are the patient-to-ground and the patient-to-power-line capacitances, usually denoted as CB and CP, respectively. A technique to estimate these elements and experimental data obtained in different environmental conditions are presented. It was found that CB ranges from hundreds of pF to nF, and CP from hundredths of pF to few pF. The presented technique also lets it know the small amplifier-to-ground and amplifier-to-power-line capacitances. The knowledge of all these capacitances allows estimating the EMI conditions that biopotential amplifiers can be subject to, thus, resulting useful data for specifying their design requirements and constraints in real working conditions.